Improving mental health care literacy in primary care: a controlled intervention study - Ângelo Emanuel Martins Rodrigues Neves (2023)
Background: Mental disorders are a significant cause of disability worldwide, accounting for over thirty percent of the burden measured in terms of disability-adjusted life years (DALY). The most prevalent cause of mental disorders burden comprises depressive, anxiety, somatoform disorders, and suicidal behaviours, collectively known as common mental disorders (CMD). Family doctors in different countries lack sufficient knowledge to recognise, diagnose, treat, and manage these disorders. Similarly, the general population also has a poor mental health literacy (MHL), making it difficult for those affected by CMDs to seek appropriate help and care. Aim: We aim to assess the effect of a combined intervention of primary care professionals' training and patients' psychoeducation on well-being of patients diagnosed with CMD (n=348) after a follow-up of twelve months, versus usual care. Methods: The general care practice is the unit of randomization of this cluster-randomised controlled trial with three units for the case arm and two for the control arm. The combined intervention consisted of an eight-hour mental health training program directed to primary care health professionals, including family doctors (n=38, 24 case and 14 control), nurses and psychologists, and the psychoeducational group of patients (n=35 in the case arm) consisted of a weekly session for 6 weeks, led by a trained non-medical primary care professional. Positive mental health putative effects were measured by the Five items Well-being Index, WHO-5. For statistical analysis we used chi-square tests to evaluate the distribution of well-being, depressive and anxiety symptoms severity within each group and for the distribution of scores between the two groups. A linear mixed model was implemented to examine the effects of time, condition (control vs. intervention), baseline and post-intervention depressive and anxiety symptoms, age, and sex on well-being. Results: Both intervention and control groups were comparable in terms of the main variables at the baseline evaluation. The results showed a significant effect of the intervention on well-being. The intervention group experienced substantial improvements in well-being, outperforming the control group. The linear mixed model analysis further confirmed the positive impact of the intervention. This indicates that the intervention not only improved well-being scores over time but did so at a significantly faster rate than the control group. Overall, the intervention, along with other predictors, accounted for approximately 41.4% of the variance in well-being scores, underscoring the potent role of the intervention in enhancing well-being. Discussion: CMD management is liable to be improved by capacitation of the primary care organizations and empowerment of patients through psychoeducation and this study demonstrates temporal sustainability of effects. Keywords: Mental health literacy; Psychoeducation; Depression; Anxiety; Somatoform; Self-harm; Common mental disorders; Primary health care